Effect of Azolla Bocachi and Liquid Organic Fertilizer of Goat Manure on the Growth and Production of Chinese Kale (Brassica oleracea L.) - Barus, Wan Arfiani; Utami, Sri; Azmi, Erna Pan (Talenta Publisher, 2018)
The purpose of this research was to find out the effect of Azolla Bokashi and liquid organic fertilizer of goat manure on the growth and production of Chinese kale. This study used a Factorial Randomized Block Design. The factors studied were Azolla Bokashi Fertilizer (B) with 3 levels (B0 = without treatment/control, B1 = 5 tons (1.14 kg/plot), B2 = 10 tons (2.28 kg/plot) and liquid organic fertilizer of goat manure (K) (K0 = without treatment, K1 = 100 ml/liter of water, K2 = 200 ml/liter of water, and K3 = 300 ml/liter of water. The parameters observed were the plant height, number of leaves, amount of chlorophyll, stem diameter, plant’s wet weight, plant’s dry weight and harvest index.